2016
DOI: 10.1177/0271678x16650218
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the ATF6 branch of the unfolded protein response in neurons improves stroke outcome

Abstract: Impaired function of the endoplasmic reticulum (ER stress) is a hallmark of many human diseases including stroke. To restore ER function in stressed cells, the unfolded protein response (UPR) is induced, which activates 3 ER stress sensor proteins including activating transcription factor 6 (ATF6). ATF6 is then cleaved by proteases to form the short-form ATF6 (sATF6), a transcription factor. To determine the extent to which activation of the ATF6 UPR branch defines the fate and function of neurons after stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 45 publications
1
72
0
Order By: Relevance
“…On the other hand, ischemic strokes are the leading cause of death, cognitive and motor dysfunction, and neurodegenerative diseases (Wei et al, 2012). Similarly, ER stress has been found in neurons after ischemic stroke (Yu et al, 2016). …”
Section: Changes Of Er Stress and Autophagy After Traumatic Brain mentioning
confidence: 78%
“…On the other hand, ischemic strokes are the leading cause of death, cognitive and motor dysfunction, and neurodegenerative diseases (Wei et al, 2012). Similarly, ER stress has been found in neurons after ischemic stroke (Yu et al, 2016). …”
Section: Changes Of Er Stress and Autophagy After Traumatic Brain mentioning
confidence: 78%
“…Xbp1 f/f mice (C57BL/6 background) were kindly provided by Dr Laurie Glimcher (Weill Cornell Medical College). 17 To delete Xbp1 in forebrain neurons, we first crossed Xbp1 f/f mice with Emx1 Cre/Cre mice (JAX stock #005628; C57BL/6 background), 8 to generate Xbp1 f/+ ; Emx1-Cre mice. These mice were then mated with homozygous floxed Xbp1 f/f mice to generate experimental animals: Xbp1 f/f ; Emx1-Cre (Xbp1-cKO) and Xbp1 f/f (control).…”
Section: Methodsmentioning
confidence: 99%
“…tMCAO was carried out as described previously. 8 Briefly, anesthesia was induced in mice with 5% isoflurane in 30% O 2 balanced with N 2 O. Mice were then orally intubated and mechanically ventilated with 1.8% isoflurane during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, expression of target genes of the three UPR branches, including GRP78, GADD153/ CHOP, ER stress protein 72 (ERp72), and PDI, is up-regulated after brain ischemia. [57][58][59][60][61][62][63] Further, splicing of Xbp1 mRNA is activated in post-ischemic brains, 14,64 and eIF2a is phosphorylated in a PERKspecific manner. 65,66 It should be noted that postischemic activation of UPR is unequivocal proof that transient ischemia impairs ER function, and is also an indicator that cells activate adaptive responses to cope with this pathologic state.…”
Section: Brain Ischemiamentioning
confidence: 99%
“…13 Recently, we have reported that a marked increase in expression of GRP78 does not modify the extent of UPR activation triggered by transient cerebral ischemia, which supports a model of UPR activation independent of GRP78 dissociation from ER stress sensor proteins. 14 Under ER stress conditions, the protein folding demand exceeds folding capacity. Activation of UPR triggers a variety of adaptive responses to restore the folding demand/capacity balance, and to clear unfolded/misfolded proteins from the ER, thereby reestablishing cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%